Evaluation of the antimalarial activity of SAM13-2HCl with morpholine amide (SKM13 derivative) against antimalarial drug-resistant Plasmodium falciparum and Plasmodium berghei infected ICR mice - Hong, Hyelee; Moon, Kwonmo; Trinh, Thuy-Tien Thi; Eom, Tae-Hui; Park, Hyun; Kim, Hak Sung; Yeo, Seon-Ju (Parasites, hosts and diseases, 2024)
Antimalarial drugs are an urgently need and crucial tool in the campaign against malaria, which can threaten public health. In this study, we examined the cytotoxicity of the 9 antimalarial compounds chemically synthesized using SKM13-2HCl. Except for SKM13-2HCl, the 5 newly synthesized compounds had a 50% cytotoxic concentration (CC50) > 100 µM, indicating that they would be less cytotoxic than SKM13-2HCl. Among the 5 compounds, only SAM13-2HCl outperformed SKM13-2HCl for antimalarial activity, showing a 3- and 1.3-fold greater selective index (SI) (CC50/IC50) than SKM13-2HCl in vitro against both chloroquine-sensitive (3D7) and chloroquine -resistant (K1) Plasmodium falciparum strains, respectively. Thus, the presence of morpholine amide may help to effectively suppress human-infectious P. falciparum parasites. However, the antimalarial activity of SAM13-2HCl was inferior to that of the SKM13-2HCl template compound in the P. berghei NK65-infected mouse model, possibly because SAM13-2HCl had a lower polarity and less efficient pharmacokinetics than SKM13-2HCl. SAM13-2HCl was more toxic in the rodent model. Consequently, SAM13-2HCl containing morpholine was selected from screening a combination of pharmacologically significant structures as being the most effective in vitro against human-infectious P. falciparum but was less efficient in vivo in a P. berghei-infected animal model when compared with SKM13-2HCl. Therefore, SAM13-2HCl containing morpholine could be considered a promising compound to treat chloroquine-resistant P. falciparum infections, although further optimization is crucial to maintain antimalarial activity while reducing toxicity in animals.